2017
DOI: 10.4236/ojrad.2017.73020
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Radiofrequency Ablation of Initial Recurrent Hepatocellular Carcinoma after Hepatectomy: Long-Term Results and Prognostic Factors

Abstract: Background: Intrahepatic recurrence of hepatocellular carcinoma (HCC) is frequently noted in patients after hepatectomy of HCC. Recurrence HCC is usually diagnosed as small nodule ≤ 2 cm in diameter due to the frequent postoperative check up with US, dynamic CT, or dynamic EOB-MRI. Radiofrequency ablation (RFA) is recommended for these small HCCs, because RFA is minimally invasive, effective, and repeatedly performed. Purpose: To investigate the long-term outcome and prognostic factors of RFA in recurrent HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recently in 2017, although performed on patients after hepatectomy, Shinozuka et al [14] concluded that Child-Pugh class (A or B) before RFA was a significant predictor of long-term survival.…”
Section: Resultsmentioning
confidence: 99%
“…Recently in 2017, although performed on patients after hepatectomy, Shinozuka et al [14] concluded that Child-Pugh class (A or B) before RFA was a significant predictor of long-term survival.…”
Section: Resultsmentioning
confidence: 99%